2004
DOI: 10.1208/aapsj060436
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized dynorphin derivatives for modulating antinociceptive activity in morphine tolerant rats: Effect of different routes of administration

Abstract: Dynorphins, such as dynorphin A(1-13) (Dyn A(1-13)), have been shown to enhance analgesia in morphine-tolerant animals, despite their very short half-life after intravenous administration. The potential use of dynorphins in humans is therefore of interest. This laboratory has recently evaluated the metabolic fate of stabilized dynorphin derivatives. This study was conducted to evaluate whether such stabilized derivatives, ie, [NMet-Tyr 1 ]-Dynorphin A(1-13) (N-MT Dyn A, stabilized at the N-terminal end) and [N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…in structural modification strategies, pulmonary delivery [23] and demonstrated activity following oral administration, hold promise that opioid peptides can be systemically administered by a variety of methods including those that don’t involve injection to yield therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in structural modification strategies, pulmonary delivery [23] and demonstrated activity following oral administration, hold promise that opioid peptides can be systemically administered by a variety of methods including those that don’t involve injection to yield therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Like the parent peptide, these analogs did not produce antinociceptive tolerance. [NMeTyr 1 ]dynorphin A-(1-13) and its C-terminal amide derivative have been shown to enhance morphine-induced antinociception in morphine-tolerant rats after systemic administration [23]. Interestingly, although the compounds were not active after s.c. administration, they were active following pulmonary delivery.…”
Section: Development Of Systemically Active Opioid Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the delivery of peptides as therapeutic agents remains a challenge, the development of alternatives to injection for systemic administration will facilitate their clinical use. The recent demonstration of the activity of Dyn A-(1-13) analogs following inhalation (38) shows that other routes of administration can be used for opioid peptides that could increase their acceptance as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…While the present study has utilized i.c.v. administration of arodyn, a number of studies have shown that dynorphin A analogs can cross the blood-brain barrier and remain active after systemic administration (Yu et al, 1997;Butelman et al, 1999;Hiramatsu et al, 2001;Brugos et al, 2004). In recent work, arodyn has been shown to cross a model of the blood-brain barrier (Chappa, Fang, Aldrich and Lunte, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%